Teaching creative thinking and problem-solving skills for a vulnerable group: the case of teenage pregnancy - Jalal Nori, Abdulwahed; Machouche, Salah; Eid, Iyad Muhammad; Mohd Zin, Najibah (2022)
Creative thinking skills are one of the most appreciated tools of leading in various domains of human life. Although most studies focus more on certain vital sectors like innovation and industry, the creative thinking skill can be considered an effective tool to be utilized in other social subjective fields that concerns focus more on the wellbeing of people by helping to solve their personal and social problems. This research aims to share a field experience of teaching creative thinking skills for 36 vulnerable young women that reside in Raudhatus Sakina Center. By adopting the Islamic framework and concept of human nature, creative thinking and creativity, the trainers were able to interact more effectively with the participants and extend the relevance of creative thinking tools to the circle of their spiritual states, feelings, mental mods, and their social relations. To create confidence and learning interest among the participants, the trainers have used various mediums like stories, Islamic calligraphy, Torrence test, and the cultural context. According to responses of the participants to the question “did program benefit you in building up your confidence and readiness to address the problems you are facing in a more positive way”, the training that lasted for 12 weeks (2hr. each week) has significantly helped them not only in learning problem-solving skills but also to develop a positive perspective in looking to the problems and the overall meaning of life.